FGF23 and Vitamin D Metabolism. (13th October 2021) - Latic, Nejla; Erben, Reinhold G.
ABSTRACT: Apart from its phosphaturic action, the bone‐derived hormone fibroblast growth factor‐23 (FGF23) is also an essential regulator of vitamin D metabolism. The main target organ of FGF23 is the kidney, where FGF23 suppresses transcription of the key enzyme in vitamin D hormone (1, 25(OH)2 D) activation, 1α‐hydroxylase, and activates transcription of the key enzyme responsible for vitamin D degradation, 24‐hydroxylase, in proximal renal tubules. The circulating concentration of 1, 25(OH)2 D is a positive regulator of FGF23 secretion in bone, forming a feedback loop between kidney and bone. The importance of FGF23 as regulator of vitamin D metabolism is underscored by the fact that in the absence of FGF23 signaling, the tight control of renal 1α‐hydroxylase fails, resulting in overproduction of 1, 25(OH)2 D in mice and men. During recent years, big strides have been made toward a more complete understanding of the mechanisms underlying the FGF23‐mediated regulation of vitamin D metabolism, especially at the genomic level. However, there are still major gaps in our knowledge that need to be filled by future research. Importantly, the intracellular signaling cascades downstream of FGF receptors regulating transcription of 1α‐hydroxylase and 24‐hydroxylase in proximal renal tubules still remain unresolved. The purpose of this review is to highlight our current understanding of the molecular mechanisms underlying the regulation of vitamin D metabolism by FGF23, and to discuss the role of these mechanisms in physiology and pathophysiology. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.